2004
DOI: 10.1096/fj.03-0826fje
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine and fibronectin expression in lung fibroblasts: implications for tobacco‐related lung tissue remodeling

Abstract: Tobacco-related lung diseases are associated with alterations in tissue remodeling and are characterized by increased matrix deposition. Among the matrix molecules found to be highly expressed in tobacco-related lung diseases is fibronectin, a cell adhesive glycoprotein implicated in tissue injury and repair. We hypothesize that nicotine, a component of tobacco, stimulates the expression of fibronectin in lung fibroblasts via the activation of intracellular signals that lead to increased fibronectin gene trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
87
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(93 citation statements)
references
References 60 publications
(69 reference statements)
6
87
0
Order By: Relevance
“…In these mice, immunohistochemical studies and luciferase detection revealed a pattern of luciferase expression in lung reminiscent of that shown by the endogenous fibronectin gene at baseline and after stimulation with nicotine. 3 We have previously reported that nicotine stimulates fibronectin expression in lung and in cultured primary lung fibroblasts (13). As expected, primary lung fibroblasts isolated from the transgenic animals showed increased expression of luciferase driven by the human fibronectin promoter when exposed to nicotine (14).…”
Section: Generation Of Mice Transgenic For the Human Fibronectin Promsupporting
confidence: 60%
“…In these mice, immunohistochemical studies and luciferase detection revealed a pattern of luciferase expression in lung reminiscent of that shown by the endogenous fibronectin gene at baseline and after stimulation with nicotine. 3 We have previously reported that nicotine stimulates fibronectin expression in lung and in cultured primary lung fibroblasts (13). As expected, primary lung fibroblasts isolated from the transgenic animals showed increased expression of luciferase driven by the human fibronectin promoter when exposed to nicotine (14).…”
Section: Generation Of Mice Transgenic For the Human Fibronectin Promsupporting
confidence: 60%
“…Fibronectin is usually mesenchymal in origin but also has been described in the epithelium during branching morphogenesis (22a). Fibronectin expression in fetal lung fibroblasts already has been shown to increase with exposure to nicotine through ␣ 7 nAChR-mediated signals (22). We found that both nicotine treatment of lung explant cultures in vitro and prenatal nicotine exposure in vivo results in increased fibronectin expression in the pseudoglandular stage lung.…”
Section: Discussionmentioning
confidence: 54%
“…Fibronectin is a known morphogen that is found in the branching clefts and is considered essential for proper branching (18, 22a). Interestingly, nicotine has been shown to stimulate fibronectin expression in fetal and adult lung fibroblasts (22). Thus we tested the effects of nicotine on fibronectin in our lung explant model.…”
Section: Distribution Of ␣mentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence that active CHRNA7 can induce lung fibroblast and regulate lung inflammation also supports it may involve the development of both diseases. 30,31 In the current study, we found that the ≥ 4-copy of CNV-3956 that duplicates the CHRNA7 gene conferred increased risks and poor prognoses of lung cancer and COPD, underlying a possible biological mechanism by increasing CHRNA7 expression and inducing carriers to consume more cigarettes because individuals with higher CHRNA7 expressions would be more nicotine sensitive. A challenge on this mechanism is that the loss genotype of CNV-32018, which we did not test due to technical limitation, would possibly induce exon deletion of CHRNA7 and nonfunctional CHRNA7, and thus the ≥ 4-copy of CNV-3956 may cause a upregulation of nonfunctional CHRNA7.…”
Section: Discussionmentioning
confidence: 55%